Building a Supportive Workplace: How Workplace Friendship and Emotional Support Foster Employee Well-being through Work-Life Balance - Dr Tariq Jamil; Dr. Muhammad Irfan Raza; Akhtar Mehmood; Dr Usman Ali; Dr Muhammad Saeed Ahmad (Social Science Review Archives, 2025)
This study explores the influence of workplace friendship on employees' psychological well-being, drawing on the conservation of resources theory to elucidate how social resources enhance well-being. The present study specifically examines the mediating role of emotional support and the moderating effect of work-life balance within this relationship. Employing a quantitative research design, data were gathered from 395 employees through a structured survey and analyzed using structural equation modeling and Hayes' Process macro. The findings reveal that workplace friendship significantly enhances psychological well-being, with emotional support partially mediating this effect. Additionally, work-life balance strengthens both the direct and indirect effects, amplifying the positive influence of workplace friendship. These results highlight the critical role of supportive workplace relationships in fostering employee well-being. The present study offers valuable insights for academics, policymakers, and organizations by highlighting the importance of workplace friendships, emotional support, and work-life balance in enhancing employee psychological well-being and productivity.